1985
DOI: 10.3177/jnsv.31.139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of riboflavin-butyrate on cardiac glutathione reductase affected by adriamycin.

Abstract: SummaryMale Wistar rats received intraperitoneal injections of adriamycin (4mg/kg body weight/day) and/or riboflavin-butyrate (20mg/kg body weight/day) for 6 consecutive days. Cardiac mitochondria were then prepared for our present experiment. The combined use of riboflavin-butyrate with adriamycin was evaluated for reduction of lipid peroxide formation in rat cardiac mitochondria. In order to find the mechanism of the effect of riboflavin-butyrate, the glutathione peroxidase glutathione reductase system was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There is some evidence suggesting that dietary supplementation with Se, vitamin E (VIT E, a-tocopherol) and riboflavin (RIB), under certain oxidative stresses (e.g., treatment with paraquat or adriamycin) may afford protection against substantial loss of cellular GSH levels (Chung & Maines 1981;Hino et al 1985;Taniguchi & Hara 1983). Yet, the available information on the potential benefit of the above nutrients as regards exposure of the CNS to HBO are not conclusive (Jamieson 1989).…”
mentioning
confidence: 99%
“…There is some evidence suggesting that dietary supplementation with Se, vitamin E (VIT E, a-tocopherol) and riboflavin (RIB), under certain oxidative stresses (e.g., treatment with paraquat or adriamycin) may afford protection against substantial loss of cellular GSH levels (Chung & Maines 1981;Hino et al 1985;Taniguchi & Hara 1983). Yet, the available information on the potential benefit of the above nutrients as regards exposure of the CNS to HBO are not conclusive (Jamieson 1989).…”
mentioning
confidence: 99%
“…However, adriamycin produces a dose-dependent cardiotoxicity that restricts its clinical use in chemotherapy. We reported that intraperitoneal administration of adriamycin induces the depletion of flavin content in rat heart mitochondria (1). The combination use of adriamycin with riboflavin was found to be effective in preventing heart mitochondrial disorders in rats treated with adriamycin (1).…”
mentioning
confidence: 98%
“…We reported that intraperitoneal administration of adriamycin induces the depletion of flavin content in rat heart mitochondria (1). The combination use of adriamycin with riboflavin was found to be effective in preventing heart mitochondrial disorders in rats treated with adriamycin (1). Therefore, the depletion of riboflavin in tissues is considered to be closely related to the administration of adriamycin .…”
mentioning
confidence: 99%